The Responsibility and Accountability of CEOs: The Last Interview with Ken Lay - Ferrell, O. C. 1943-; Ferrell, Linda (2011)
Responsibility and accountability of CEOs has been a major ethical concern over the past 10 years. Major ethical dilemmas at Enron, Worldcom, AIG, as well as other well-known organizations have been at least partially blamed on CEO malfeasance. Interviews with Ken Lay, CEO of Enron, after his 2006 fraud convictions provides an opportunity to document his perceived role in the demise of Enron. Possibly no other CEO has had as much impact on the scrutiny and legalization of business ethics as Ken Lay. This analysis is timely because of many information sources now available and the recent Supreme Court decisions on Enron conviction appeals. Using Ken Lay as the focal point, a review of literature provides the background for research questions to explore the role of the CEO in developing an ethical corporate culture.
Keywords: legalization of business ethics; Enron; Jeff Skilling; Ken Lay; honest services fraud; Ethical Leadership